4q+6=-3q-43

Simple and best practice solution for 4q+6=-3q-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4q+6=-3q-43 equation:


Simplifying
4q + 6 = -3q + -43

Reorder the terms:
6 + 4q = -3q + -43

Reorder the terms:
6 + 4q = -43 + -3q

Solving
6 + 4q = -43 + -3q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '3q' to each side of the equation.
6 + 4q + 3q = -43 + -3q + 3q

Combine like terms: 4q + 3q = 7q
6 + 7q = -43 + -3q + 3q

Combine like terms: -3q + 3q = 0
6 + 7q = -43 + 0
6 + 7q = -43

Add '-6' to each side of the equation.
6 + -6 + 7q = -43 + -6

Combine like terms: 6 + -6 = 0
0 + 7q = -43 + -6
7q = -43 + -6

Combine like terms: -43 + -6 = -49
7q = -49

Divide each side by '7'.
q = -7

Simplifying
q = -7

See similar equations:

| -2m+7=2m-1 | | 5h=4x | | 8e-3=5e-9 | | 17d-3=9d+45 | | 2p+9=6p-27 | | 9t+10t=38 | | -c+2=-6c-13 | | 654/15 | | -2w+1=-7w+41 | | 5h=3x+150 | | -2f-6=-5f-3 | | 11d+5=3d-3 | | 7z-6=3z+4 | | -8k+4=-6k+20 | | 9j-4=5j+28 | | -6u+7=u+70 | | y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 |

Equations solver categories